2014
DOI: 10.1093/heapol/czu070
|View full text |Cite
|
Sign up to set email alerts
|

How people-centred health systems can reach the grassroots: experiences implementing community-level quality improvement in rural Tanzania and Uganda

Abstract: Community-level QI is a participatory research approach that engaged volunteers in Tanzania and Uganda, putting them in a central position within local health systems to increase health-seeking behaviours and improve preventative maternal and newborn health practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Unlike other studies conducted in Ethiopia, Bangladesh, and India [37][38][39], this study indicated that community participation had a positive effect on PNC coverage. This might be due to improving HEW home visits regularity, which is supported by previous studies showing that community participation improved the accountability of health care providers [33,63], and improved birth notification systems and practices of keeping women at facilities for at least 24 hours after delivery for PNC.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike other studies conducted in Ethiopia, Bangladesh, and India [37][38][39], this study indicated that community participation had a positive effect on PNC coverage. This might be due to improving HEW home visits regularity, which is supported by previous studies showing that community participation improved the accountability of health care providers [33,63], and improved birth notification systems and practices of keeping women at facilities for at least 24 hours after delivery for PNC.…”
Section: Discussionmentioning
confidence: 67%
“…For policy makers and donors to be convinced by costing data, they must first be convinced of the benefits of what is being costed, and this has created a challenge for QI approaches generally. We have not presented data on the individual improvements achieved by the 29 improvement teams included in our study, which are similar to those observed by other community QI projects from several settings in sub-Saharan Africa 31–34 61–65. Immediate process outcomes of the QI approach we used included: improved supervision and integration of the community health programme to the health system, consensus building across levels of the health system on priority problems and improved data quality on critical health service areas—all of which have been shown to support improved performance of CTC providers 5 9 43 66 67.…”
Section: Discussionmentioning
confidence: 90%
“…Policy makers are beginning to question whether CTC providers can achieve equitable service quality at low cost 29. Evidence is growing for systematically incorporating quality improvement (QI) approaches into community health programmes in low-income and middle-income countries, especially in maternal and child health 30–34. These community-level approaches appear to have been successful in terms of improving the quality and equity of services, but there is limited information about costs or cost-effectiveness of implementation 32 34.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the primary volunteer activities of communitylevel quality improvement were attending learning sessions, attending monthly meetings, and creating, implementing, testing, and monitoring change ideas using PDSA cycles. For more information, communitylevel quality improvement within EQUIP is described in greater detail elsewhere (Tancred et al, 2014 Overall total /100…”
Section: Community-level Interventionmentioning
confidence: 99%